(untitled) (Libellarium: časopis za istraživanja u području informacijskih i srodnih znanosti, 2017)
Research data or datasets can be regarded as a catalyst to inspire new research by repurposing or combining existing research data, and grant applicants have been requested by funding institutions to include a data management plan as part of research project proposals. In addition to the metadata approach, data papers may mirror the scientific publication model as an alternative means of description and management of research data. However, there is not a common standard for all data papers across various communities. This study aimed to build up a common structural framework to investigate the embedded characteristics and structures of the content of data papers by using a content analysis approach, and 26 data journals from 16 publishers were selected as subject in this study. This study has proposed a common framework and further embodied a concept map (Candela et al. 2015) into more concrete components for the structure of data papers.